Colloids and Interfaces in Life Sciences and Bionanotechnology, Second Edition. - Norde, Willem (CRC Press, 2011)
Each chapter includes Exercises and Suggestions for Further ReadingIntroductionColloidal DomainInterfaces Are Closely Related to ColloidsColloid and Interface Science in a Historical PerspectiveClassification of Colloidal SystemsColloidal Particles: Shapes and Size DistributionsShapesParticle Size DistributionsAverage Molar Mass. Specific Surface AreaSome Thermodynamic Principles and Relations, with Special Attention to Interfaces Energy, Work, and Heat: The First Law of Thermodynamics The Second Law of Thermodynamics: EntropyReversible Processes: Definition of Intensive VariablesIntroduction o.